PENGARUH KUALITAS LAYANAN, CITRA MEREK, KEWAJARAN HARGA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN TOKO DOKTER KOMPUTER - Sartika, Desta Pasura; Mahmud, Mahmud; Aqmala, Diana; Setiawan, Aries (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to examine the impact of service quality, brand image, and price fairness on customer satisfaction and loyalty at Dokter Komputer Store in Semarang. Using a quantitative approach, data were collected through questionnaires from 195 respondents selected via purposive sampling. The analysis, conducted using the SEM method with SmartPLS, revealed that these three factors positively and significantly influence customer satisfaction, which in turn has a direct impact on customer loyalty. These findings suggest that computer service providers should improve service quality, strengthen brand image, and set fair prices to enhance customer satisfaction and loyalty.